Insect Community Structure in Corn Plantations and the B.J. Habibie Forest Park (Tahura) - Nazwa H. Djafar; Chairunnisah J. Lamangantjo; Mustamin Ibrahim; Ilyas H. Husain; Abubakar Sidik Katili (Bantara Journal of Animal Science, 2026)
The conversion of forest land into cornfields in the Bontula Village Buffer Forest, Tahura BJ Habibie, has caused changes in vegetation and environmental conditions that have impacted insect diversity. This study aims to analyze the structure of insect communities in the buffer forest habitat and the corn fields in Bontula Village. The study employed a quantitative descriptive method with a comparative approach. Sampling was conducted using purposive sampling with a combination of pitfall traps and light traps. The collected insects were identified to the species level and then analyzed using the Shannon-Wiener diversity index (H'), abundance (Di), evenness (E), species richness (R), and dominance (D). The results showed that 1,460 insect individuals belonging to 24 species and 21 families were found. The diversity index value for the buffer forest (H' = 1.376) was higher than that for the corn plantation (H' = 1.091), but both fell into the moderate category. The species with the highest abundance was Novomessor cockerelli, with a Di value of 0.415% in the buffer forest and 0.588% in the corn plantation. The evenness index was moderate, with a value of E = 0.508 in the buffer forest and E = 0.439 in the corn plantation. The species richness indices were R = 2.031 and R = 1.784, respectively, while the dominance indices were D = 0.302 and D = 0.441. In general, the insect community structure in both habitats was relatively stable, with a fairly good ecological balance.